Desenvolvimento e caracterização de microcápsulas de casca de jabuticaba (Myrciaria Cauliflora Berg) - Santos, Michele Arias Delfino dos (2018)
The substitution of synthetic dyes by natural ones is an object of interest both for the food industry and for consumers, valuing the functional properties attributed to these compounds. Anthocyanins are natural pigments that confer attractive colors and potential health benefits, being present in great amount in jabuticaba peel. Microencapsulation is an alternative for improving the stability of pigments and enabling their use in products. The objective of the present work was to obtain capsules of jabuticaba peel extract by spray dryer, evaluating the water activity, moisture, yield of powder, solubility, wettability, encapsulation efficiency, anthocyanin retention and color. In all assays, microcapsules with low water activity and moisture were obtained. The yield ranged from 12.58% to 36.05%, being the assay using only gum arabic as the wall material, with the highest yield. All assays showed high solubility. Regarding encapsulation efficiency and anthocyanin retention, it was observed that the assay using only gum arabic was the one that obtained the highest values. By color analysis, it was observed that the microcapsules presented difference in relation to the extract. Thus, these results indicate a possibility of using these microcapsules as a dye in food products, as a way to obtain benefits and add value to the product.